Twice-daily rivaroxaban after percutaneous left atrial appendage closure for atrial fibrillation - Pan, Yang-Qi; Jin, Lu-Shen; Qian, Sang; Jiang, Ting; Wang, Zhe-Ning; Chen, Yi-Lian; Qiu, Yi-Xuan; Wu, Yi-Hao; Fu, Jia-Yang; Li, Ling; Lin, Yuan-Nan; Li, Yue-Chun (Frontiers in Pharmacology, 2024)
Background and aim: Rivaroxaban is an emerging oral anticoagulant for postoperative anticoagulation after percutaneous left atrial appendage closure (LAAC). Because a once-daily dosing regimen of rivaroxaban causes fluctuations in the drug plasma concentration, we studied the feasibility and safety of twice-daily rivaroxaban as a postoperative anticoagulation regimen for patients with atrial fibrillation (AF) undergoing LAAC. Methods: This study involved patients with AF who underwent LAAC and took rivaroxaban postoperatively. A total of 326 patients who received a standard total dose (15 or 20 mg) of rivaroxaban based on their creatinine clearance rate were divided into the twice-daily (BID) rivaroxaban group (n = 208) and once-daily (QD) rivaroxaban group (n = 118) according to their anticoagulation strategy. Transesophageal echocardiography was recommended at 3 to 6 months postoperatively to check for device-related thrombosis (DRT). Clinical outcomes were evaluated during postoperative anticoagulation. Results: The median CHA2DS2-VASc score (4 [3, 5] vs. 4 [3, 5], P = 0.28) and HAS-BLED score (2 [2, 3] vs. 2 [2, 3], P = 0.48) were not significantly different between the groups. During the anticoagulation period (4.1 ± 0.7 vs. 4.1 ± 0.9 months, P = 0.58), 148 (71.2%) patients in the BID group and 75 (63.6%) in the QD group underwent follow-up transesophageal echocardiography. There were no statistically significant differences between the two groups in terms of DRT (1.4% vs. 2.7%, P = 0.60), minor bleeding (8.2% vs. 11.0%, P = 0.39), thromboembolic events (1.0% vs. 0.8%, P = 1.00), major bleeding (0.5% vs. 0.8%, P = 1.00), or death. Conclusion: A short course of twice-daily rivaroxaban following LAAC is a feasible alternative regimen with a low rate of major bleeding events, DRT, and thromboembolic events for patients with AF.